ADVANCEMENT AND APPLICATIONS OF GENE EDITING TOOLS FOR CROP IMPROVEMENTS: The Contemporary (FUDMA JOURNAL OF SCIENCES, 2023)
Advancements in gene editing tools have transformed the fields of the agricultural system and crop improvement; thus, editing tools have been adopted rapidly in the research community. The deletion “Insertion” of DNA may be described, more precisely, as gene editing. Zinc-finger nuclease (ZFN) was the first technique used to cut DNA, later, ZFN+TALEN (transcription activator-like effectors nucleases) uses to target specific DNA, but the practical problem became an issue with this technology. A new advanced tool, “clustered regularly interspaced short palindromic repeats” (CRISPR) solved that problem, with the requirement of nuclease called CAS9 and a piece of ribonucleic acid (RNA). Crop production is facing many challenges such as climate change, salinity, drought, low grain quality, yield, post-harvest loss, low nutrient use efficiency, pest and diseases among others, hence achieving sustainable and secure crop products became a complex network requiring a multi-faceted solution. Recognised means to address these issues is to develop tolerant and high yield varieties using conventional and modern breeding techniques through genetic engineering by introducing desirable traits in crops. Despite many attempts using different strategies for crop improvements, the achievements so far are quite modest. Gene editing tools can be used to enhance crop improvement by allowing the prologue of precise and predictable changes directly in an elite milieu and the CRISPR system is constructive for multiple traits and simultaneous modification. This review paper aims to discuss the most recent advance of gene editing technique and its application in crop improvement as well as challenges that hinder its
Keywords: Advancement: CRISPR: Crop improvement: Gene editing technology: ZFN TALEN